Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Pertambahan Nilai di Kantor Pelayanan Pajak Pratama Tulungagung - Zulkifli Rahman Susanto; Novi Khoiriawati (Politeknik Negeri Bengkalis, 2022)
This study aims to examine the effect of tax audit and tax collection on Value Added Tax revenue at KPP Pratama Tulungagung. The data collection technique is by using questionnaire data distributed to Taxable Entrepreneurs who have experienced inspection and billing. The method used by the researcher is using a quantitative approach with associative research type. The results of this study indicate that partially tax audit has a positive and significant effect on Value Added Tax revenue at KPP Pratama Tulungagung and tax collection has a positive and significant effect on Value Added Tax revenue at KPP Pratama Tulungagung. Simultaneously, tax audit and tax collection have a positive and significant effect on the value added tax revenue at KPP Pratama Tulungagung.Keywords: Tax Audit, Tax Collection, Value Added Tax